Stability of Moringa Seed Oil Compared to Some Vegetable Oils in Sudan - Elhassan Babiker, Babiker M.; Saad Shakak, Mahdi Abbas (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study was conducted to see general characteristic and stability of moringa seed oil in comparison with oils of groundnut, sunflower and cottonseeds in frequent frying process. Moringa seed oil was purchased from Omdurman local Market. Refractive index, density viscosity, colour red, yellow and blue and oil content which were 1.4640, 0.9190, 20.22, cp 5.00, 1.30, 0.00 and38.6% receptively. The chemical properties of moringa seed oil showed peroxide value 2.79 meqO2/kg , free fatty acids 1.40% and fatty acid composition exhibited oleic, linoleic, stearic, behenic and palmatic acids (45.09 , 42.43 , 8.38 , 1.77 , 0.52%) respectively. There were significant difference (p ≤ 0.05 )among refractive index , density , viscosity colour of moringa seed oil when they compared to sunflower seed , cottonseed , and groundnut oils before frying and after frying periods . Also there were significant difference in chemical properties among peroxide value and free fatty acids of moringa seed oil compared to sunflower, cottonseed and ground nut oils before frying and after frying time, also there was significant difference in sensory characteristics of taste, flavour, colour, texture and over all acceptability of potato chips fried in moringa seed oil compared to sunflower seed, cotton seed and groundnut oils .It is observed that potatoes chips fried by moringa oil was better than those fried by other oils.